British Thoracic Society guidelines for the management of community acquired pneumonia in children: update 2011. - Harris, M; Clark, J; Coote, N; Fletcher, P; Harnden, A; McKean, M; Thomson, A (2011)
The British Thoracic Society first published management guidelines for community acquired pneumonia in children in 2002 and covered available evidence to early 2000. These updated guidelines represent a review of new evidence since then and consensus clinical opinion where evidence was not found. This document incorporates material from the 2002 guidelines and supersedes the previous guideline document.